Mucin‐Inspired, High Molecular Weight Virus Binding Inhibitors Show Biphasic Binding Behavior to Influenza A Viruses. Issue 47 (1st November 2020) - Wallert, Matthias; Nie, Chuanxiong; Anilkumar, Parambath; Abbina, Srinivas; Bhatia, Sumati; Ludwig, Kai; Kizhakkedathu, Jayachandran N.; Haag, Rainer; Block, Stephan
Abstract: Multivalent binding inhibitors are a promising new class of antivirals that prevent virus infections by inhibiting virus binding to cell membranes. The design of these inhibitors is challenging as many properties, for example, inhibitor size and functionalization with virus attachment factors, strongly influence the inhibition efficiency. Here, virus binding inhibitors are synthesized, the size and functionalization of which are inspired by mucins, which are naturally occurring glycosylated proteins with high molecular weight (MDa range) and interact efficiently with various viruses. Hyperbranched polyglycerols (hPGs) with molecular weights ranging between 10 and 2600 kDa are synthesized, thereby hitting the size of mucins and allowing for determining the impact of inhibitor size on the inhibition efficiency. The hPGs are functionalized with sialic acids and sulfates, as suggested from the structure of mucins, and their inhibition efficiency is determined by probing the inhibition of influenza A virus (IAV) binding to membranes using various methods. The largest, mucin‐sized inhibitor shows potent inhibition at pm concentrations, while the inhibition efficiency decreases with decreasing the molecular weight. Interestingly, the concentration‐dependent IAV inhibition shows a biphasic behavior, which is attributed to differences in the binding affinity of the inhibitors to the two IAV envelope proteins, neuraminidase, and hemagglutinin. Abstract : Multivalent virus binding inhibitors are synthesized, the size and functionalization of which are inspired by mucins. Inhibition studies using influenza A viruses show potent inhibition that increases with increasing inhibitor size. A biphasic inhibition profile is observed, indicating different inhibitor binding affinities to the envelope proteins hemagglutinin and neuraminidase and a mode of action that depends on the inhibitor concentration.